Follow-up Comparison of the Effect of Eight-weeks Corrective Exercises With and Without Myofascial Release on Postural Kyphosis Deformity - Seyed Hossein Mousavi; Hooman Minoonejad; Reza Rajabi; Foad Seidi (Sport Sciences and Health Research)
Introduction: The present research aimed to compare and follow-up the effect of 8-week corrective exercises with and without the myofascial release on functional kyphosis deformity in young adults. Methods: It was a randomized controlled trial in the university laboratory. Forty-five male students suffering from abnormal hyperkyphosis deformity (kyphosis of more than 42°) were selected and randomly assigned to three groups: corrective exercises, combinational exercises (corrective and myofascial release), and control. The Mean±SD age, height, and weight of the study sample were 22.12±2.88 years, 175.44±6.80 cm, and 71.21±7.31 kg, respectively. The study groups did the exercises for 8 weeks, under the direct observation of the researchers. The kyphosis angle of the participants was measured using a flexible ruler, at the baseline, post-test, and follow-up (4 weeks after the end of the exercises) stages. The collected data were analyzed with repeated measures Analysis of Variance (ANOVA) and Analysis of Covariance (ANCOVA) tests. Results: After 8 weeks of exercises, the degree of kyphosis in the post-test and follow-up stages was significantly lower than that in the pre-test, in both training groups. The results of the ANCOVA test demonstrated that the thoracic kyphosis degree in the combinational exercises group was significantly lower than that of the corrective exercises group (P≤0.05), in the post-test and follow-up stages. Conclusion: According to the results, the corrective exercises program in combination with the myofascial release is more effective than the corrective exercises alone, in correcting the thoracic kyphosis deformity.